Redes e intercambio de capitales en condiciones de pobreza: dimensión relacional y dimensión vincular. - Gutiérrez, Alicia B. (REDES: Revista Hispana para el Análisis de Redes Sociales, 2008)
This paper refers to the study of the social networks involved in the strategies of social reproduction of poor families, in the view of theoretical discussions as well as empirical analysis.In the first place I explain the concept of network and social capital that I utilize in my investigations, emphasizing the way in which they insert themselves within a wider problematic: that of the strategies of social reproduction in poverty, within the framework of a structural analysis.In the second place, I mention the different types of networks built empirically, that allow visualizing distinct interchanges of capitals. Here I present a concrete analysis of one of them that articulates a group of families living in a poor neighborhood of Cordoba with other agents (a group of militants of Montoneros) that occupy another position in the social space.Finally, I propose a double analytical dimension to study the social networks: a relational dimension that allows to observe the material and symbolic conditions, outsiders and incorporated, that make them possible and another one, a bonding condition, that permits to attack concretely the frequency and intensity of interactions and the types of goods and services that circulate among them.